Strategi Pedagogik Guru SMP Yakha dalam Mengelola Kelas Literasi pada Gerakan 15 Menit Membaca - Winka Naida; Dioka Muhammad Akbar; Umi Kulsum; Syifa Sifiatun Aisya (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aimed to enhance the capacity of teachers at SMP Yakha in managing literacy classes within the 15-Minute Reading Movement through the implementation of creative and participatory pedagogical strategies. The program employed a Participatory Action Research (PAR) approach consisting of four stages: planning, action, observation, and reflection. The activities began with a needs assessment, followed by literacy strategy workshops, classroom implementation assistance, monitoring, and collaborative evaluation with teachers. The results demonstrated an improvement in teachers’ competencies in applying scaffolding techniques, reading aloud, and discussion prompts, enabling them to play a more active role as literacy facilitators. In addition, students showed greater engagement in reading activities, improved reading comprehension, and enhanced critical reflection skills. The program also produced a draft Standard Operating Procedure (SOP) for literacy class management to support the sustainability of literacy culture within the school.